2015
DOI: 10.1681/asn.2013060584
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genetic Targeting of Embryonic Kidney Progenitor Cells Ex Vivo

Abstract: The embryonic mammalian metanephric mesenchyme (MM) is a unique tissue because it is competent to generate the nephrons in response to Wnt signaling. An ex vivo culture in which the MM is separated from the ureteric bud (UB), the natural inducer, can be used as a classic tubule induction model for studying nephrogenesis. However, technological restrictions currently prevent using this model to study the molecular genetic details before or during tubule induction. Using nephron segment-specific markers, we now … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 50 publications
1
63
0
Order By: Relevance
“…The organoids are known as cellular aggregates containing more than one cell type typical for the organ they replicate [18]. Such organoids have successfully been constructed with the use of primary kidney cells [1921]. …”
Section: Introductionmentioning
confidence: 99%
“…The organoids are known as cellular aggregates containing more than one cell type typical for the organ they replicate [18]. Such organoids have successfully been constructed with the use of primary kidney cells [1921]. …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is substantial experimental evidence supporting the notion that the sorting of NP cells between the tip and corner regions is established by cell-cell adhesion differences and both inductive and chemotactic molecular signalling from the ureteric bud epithelia (Brown et al, 2013;Karner et al, 2011;Lefevre et al, 2017). Previous studies identified cellcell adhesion molecules such as cadherins, to drive cell sorting (Junttila et al, 2015;Lefevre et al, 2017). Extracellular signals inducing NP cell commitment involve the secretion of WNT11, BMP7, FGF9, and WNT9B, which upregulates Wnt4 (Bohnenpoll and Kispert, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments we used organoids derived from primary cell cultures isolated from embryonic metanephric mesenchyme, as described by Junttila et al (2015), except that 10 µM BIO (6-bromoindirubin-3′-oxime, Sigma) was used for induction.…”
Section: Methodsmentioning
confidence: 99%